CHILD ABUSE AND THE DEVELOPMENT OF CHARACTER IN MISTRESS MASHAM’S REPOSE - Nurul Hikma; Burhanuddin Arafah; Herawaty Abbas (Universitas Hasanuddin, 2022)
This paper aims to elaborate on the effects of child abuse and its relationship to the development of the characters in T.H. White’s Mistress Masham’s Repose using Miller’s theory. The data were collected from the text of Mistress Masham’s Repose by T.H White. The descriptive-qualitative analysis was employed in this research. The analysis focuses on the main character responses to manipulation in order to meet adults’ need, and the behaviour shown by the main character such as repressed feeling, destructive action and also the influence of a helping witness on children.